Office 365 overview - Walsh, Heather; Safari eBooks ([Place of publication not identified] : CompuWorks, 2016)
"This course is designed to give an overview of Office 365 features, functionality, and navigation of the online environment. Microsoft Office 365 is a productivity suite that allows a user to access to Word, Excel, PowerPoint, Outlook, OneNote and many other Office tools and features online from any device with an Internet connection. Office 365 helps facilitate sharing and collaboration with online documents. Learn to sign into Office 365 from anywhere, and navigate the Office 365 environment like a pro. Learn to customize the environment to your specifications, and earn how to download the Office apps to your mobile device."--Resource description page.
Presenter, Heather Walsh.
Title and publication information from resource description page (Safari, viewed November 4, 2016).
Keywords: Microsoft Office; Integrated software; Electronic books